Impact of Social Media Marketing on Consumer Buying Behaviour of Youth - Phusalux, Jongdee; Jermsittiparsert, Kittisak; Saisama, Chompoo; Wongjunya, Naiyana (International Journal of Psychosocial Rehabilitation, 2020)
Purpose The aim of the study is to analyse the impact of social media in consumer buying behaviour of the youth in Malaysia. Design/Method/Approach: This research has adopted a primary quantitative design where the data instrument used was close ended survey. The questionnaire was distributed among 300 youth consumers where it was filled by 289 Malaysian consumers belonging to the age group of 18-24. The survey was analysed with the help of structural equation model (SEM) on Smart PLS model while considering the involvement of moderation in the model. The independent variable used in this research was Social Media Marketing which was analysed via five sub-variables: entertainment, interaction, trendiness, WoM, and customization. The dependent variable in the study was consumer behaviour which was measured by three sub-variables: brand preference, brand loyalty, and willingness to pay a premium price. The moderating effects of brand equity are assessed with the determinants of social media marketing on the components of consumer behaviour. Findings: The findings of the study revealed that the WoM in the social media marketing was the most significant factor in affecting the consumer behaviour as it positively influenced brand preference, brand loyalty and willingness to pay a premium price. In addition, there were other determinants as well, such as interaction, entertainment and customization that significantly affected the components of consumer behaviour. The variable trendiness was excluded due to high discriminant validity with other variables. Lastly, brand equity is only found to have moderating effects with entertainment on brand loyalty and willingness to pay a premium price. Practical Implications: The major limitation of this research can be considered its generalizability beyond the Malaysian consumers. Considering the entire sample constitutes of Malaysian consumers only, the results cannot be necessarily applicable to consumers belonging to other regions. Thus, the practical implication of this research is limited to Malaysian youth.